AKIBAT HUKUM DALAM PENETAPAN PENGAMPUAN PENYANDANG DISABILITAS DI PENGADILAN - Fahmi, Muhammad Nur; Rustamaji, Muhammad (Verstek, 2023)
Every human being according to law has the same rights and obligations, but not all of them are capable of carrying out legal actions. For persons with disabilities in carrying out legal actions they are under the protection of this article. The research method was carried out using a descriptive normative approach. Legal materials in the form of documents from library studies, court decisions. Analysis by examining the legal consequences arising from the judge's decision No. 53/Pdt. P/2020/PN Slw Tegal. The results of the study show that the legal consequence of determining the granting of disability by the court is in the form of giving the guardian authority to take legal action. Persons with disabilities are no longer able to carry out legal actions and in carrying out legal activities are carried out by supervisors. The custodian has the responsibility to carry out the mandate to protect those who are assisted in carrying out legal actions.Keywords: Judge's Consideration; Determination of Amnesty; Disabilities